June 10th 2007 : After the Halcyon Years... Stormy days for the PS - Delwit, Pascal (Annual Review 2008-2009. The bizarre political world of Belgium. Social Democrats at a turning point? : electoral defeat in june 2007)
"Pascal Delwit"